Tétano acidental, um problema de saúde pública susceptível de controle - FERREIRA, Denise Milioli (2001)
Accidental tetanus is a millenary disease of high lethal indices, even when proven and effective, low cost prophylactics are available. Several studies have tried to identify the physiopathological process which releases the succession of clinical manifestations of the disease. The objective of these studies is to recognize and make available a new strategy for the treatment of tetanus after exposition to the toxin. The diagnosis of tetanus is eminently clinical. Several factors may occur during the evolution of the disease which complicate its prognosis. The most frequent complications are infections and autonomic dysfunction. Several therapeutic options exist. However, they have a supportive and symptomatic role. This study has as its objective to show the complexity which involves the physiopathological process and treatment of accidental tetanus as well as to emphasize that the only effective way of reducing tetanic mortality is, doubtless, a better vaccine coverage of susceptible individuals. NOTE: Essay with review articles. This is the sum of the first.